Pengaruh Brand Image, Harga dan Promosi Terhadap Minat Beli Produk Kosmetik Wardah: (Studi Pada Chacha Kosmetik Tlogosari Semarang) - Ersa Fadilla Darmawati Putri; Heri Prabowo; Bayu Kurniawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to analyze and prove the influence of brand image, price and promotion on buying interest in Wardah cosmetic products (study on chacha cosmetics Tlogosari Semarang). This type of research is quantitative, the population of this research is consumers of the Chacha Cosmetics Tlogosari Semarang shop with a total of 96 respondents. This research uses a non-probability sampling technique, namely purposive sampling. Measurements in this study used a Likert scale which was then processed using the IBM SPSS Statistics version 23 for Windows analysis tool. The results of this research show that there is an influence between brand image, price and promotion on purchasing interest.